PERSEPSI MASYARAKAT TERHADAP PEMBANGUNAN PLTU DI DESA UJUNGNEGORO KECAMATAN KANDEMAN KABUPATEN BATANG (KAJIAN TINGKAT PENDIDIKAN) - Renita Heni Supyana (Jurnal Geografi : Media Informasi Pengembangan dan Profesi Kegeografian, 2016)
This study aimed to know the effect of educational level to people’s perceptions about PLTU development inUjungnegoro village. The sampling used simple random sampling technique. The samples were 51KK whosehouses had the nearest distance with the construction project. The data collection method used questionnaireand it was used to obtain the data of educational level, people’s knowledge of PLTU, the implementation ofsocialization, and people’s reaction toward the PLTU development. The technique of data analysis used apercentage descriptive and statistic analysis (regression). The result of this study showed that there is aneffect of educational level to the people’s perception toward the PLTU development for 33.7%. With thesignificance level of 5%,